Immediate Unilateral Breast Reconstruction using Abdominally Based Flaps: Analysis of 3,310 Cases - Kwok, Alvin C.; Simpson, Andrew M.; Ye, Xiangyang; Tatro, Eric; Agarwal, Jayant P. (Journal of Reconstructive Microsurgery, 2019)
Background The abdomen is the most common area from which tissue is harvested for autologous breast reconstruction. We sought to examine national data to determine the differences in total hospital charges, length of stay (LOS), and early postoperative complications following pedicled transverse rectus abdominis myocutaneous flap (pTRAM), free TRAM (fTRAM), deep-inferior epigastric perforator (DIEP), and superficial inferior epigastric artery perforator (SIEA) flaps.Methods The 2009–2013 Nationwide Inpatient Sample Database was used to identify patients who underwent a unilateral mastectomy and only one type of abdominally based autologous flap (pTRAM, fTRAM, DIEP, and SIEA) during the same hospital admission. Outcomes of interest included total charges, LOS, and complications including revision of vascular anastomosis and hematoma.Results A total of 3,310 cases were identified, corresponding to 15,991 abdominally based unilateral immediate breast reconstructions after standard weighting was applied; 5,079 (31.8%) were pTRAM flaps, 4,461 (27.9%) were fTRAM flaps, 6,206 (38.8%) were DIEP flaps, and 245 (1.5%) were SIEA flaps. The mean total charges for pTRAM, fTRAM, DIEP, and SIEA flaps were $17,765.5, $22,637.6, $25,814.6, and $26,605.2, respectively (p < 0.0001). The mean LOS for pTRAM, fTRAM, DIEP, and SIEA flaps were 96.5, 106.5, 106.7, and 108.9 hours, respectively (p = 0.002). The rates for return to the OR for the revision of a vascular anastomosis for pTRAM, fTRAM, DIEP, and SIEA were 0.0%, 1.72%, 2.66%, and 5.64%, respectively (p < 0.0001).Conclusions There is variation in the total charges, LOS, and early complications between pTRAM, fTRAM, DIEP, and SIEA flap-based breast reconstruction. fTRAM, DIEP, and SIEA flaps incur higher hospital total charges, have longer lengths of stay, and experience more immediate complications compared with pTRAM. Well-designed prospective trials are required to better understand the findings from this study with the inclusion of other critical outcomes such as patient satisfaction, aesthetic results, and long-term outcomes such as abdominal wall morbidity.
Keywords: breast reconstruction; microsurgery; free flaps